The Wite Way Forward: Learners’ Experiences on the Utilisation of Artificial Intelligence Tools In Research Writing - Navarette, Norman; ELAN, HAYA JANE (International Journal of Language and Literary Studies, 2025)
This phenomenological study investigates the experiences of Senior High School learners at Glan School of Arts and Trades in utilizing Artificial Intelligence (AI) tools for research writing. Since there are limited studies on AI in K-12 research writing in the Philippines, I conducted in-depth interviews with eight purposively selected learners that delve into their perceptions, challenges, and benefits associated with AI tool usage. The findings reveal a complex interplay of advantages and concerns. While learners appreciate AI's capacity to enhance grammar, generate ideas, and manage citations, they also express concerns regarding overreliance and potential ethical implications, such as plagiarism and lack of original thought. The study highlights the need for a balanced approach to AI integration in academic research, emphasizing the importance of human oversight and critical evaluation. This study contributes to the growing body of research on AI in education, providing valuable insights into the experiences and perspectives of young learners. By understanding the benefits and limitations of AI tools, educators can develop strategies to support students in using these technologies responsibly and effectively. Furthermore, the findings of this study can inform the development of guidelines and policies for the ethical and appropriate use of AI in educational settings.